Strategi Distribusi Artikel di Facebook Page Kompas.com dalam Mengoptimalkan Engagement Audiens - Amirah Inas; Vivien Febri Astuti; Tasya Camila Hamdani (MUKASI: Jurnal Ilmu Komunikasi, 2026)
Social media has become the primary channel for news distribution in the digital age, with Facebook being one platform utilized by Kompas.com to expand its reach and increase audience engagement. This study aims to identify the article distribution strategy on Kompas.com's Facebook page and its effectiveness in optimizing audience engagement. The research uses a qualitative approach through active participation, observation, interviews, and analysis of Facebook insight data for the period of October-November 2025. This research is based on the Agenda Setting Theory, which emphasizes the role of the media in shaping public issues, and the Uses and Gratifications Theory, which explains that audiences are active on digital media to fulfill personal needs. The results revealed that Kompas.com's distribution strategy, which includes article selection, caption and call-to-action (CTA) composition, use of visuals, hashtags, and timely uploads, proved effective in optimizing audience engagement, as evidenced by increased interaction from October to November 2025. This strategy successfully expanded the public reach, met the needs of the audience in the digital space, and maintained the relevance of Kompas.com as a news media in the digital space.